2018
DOI: 10.22631/ijaep.v7i2.219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training and Gender on Plasma Irisin, Leptin, and Insulin Levels

Abstract: The objective of this study is the comparison of the irisin, leptin, and insulin hormone levels of the female and male elite taekwondo athletes and non-athletes. Elite taekwondo athletes (7 males, 6 females) and university students (8 males, 6 females) between the ages of 16 and 20 who do not do exercise regularly and who are moderately active have taken part in the study. In the beginning of the study, the body compositions of the participants were determined and their plasma irisin, leptin, and insulin hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Insignificant differences were also seen between bodybuilder men and women and control women and between bodybuilder women, control women, and control men. In this study, gender did not affect irisin concentrations, which is consistent with other studies that encountered no significant main or interaction effect of gender on the irisin [21,22]. It was also found that the circulating irisin of men and women are almost similar [17,23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Insignificant differences were also seen between bodybuilder men and women and control women and between bodybuilder women, control women, and control men. In this study, gender did not affect irisin concentrations, which is consistent with other studies that encountered no significant main or interaction effect of gender on the irisin [21,22]. It was also found that the circulating irisin of men and women are almost similar [17,23].…”
Section: Discussionsupporting
confidence: 92%
“…Huh et al [22] used middle-aged women, while Stengel et al [17] omitted those under the age of 18, and Huh et al [25] included adolescents as participants. Moreover, a small sample size of elite taekwondo competitors (7 males and 6 females) and college students (8 males and 6 females) between the ages of 16 and 20 were the participants in a recent study [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. In our study results show that irisin levels at rest are not affected by training status and/or regular exercise training (41). Kurdiova et al (2014) determined that long-term chronic exercises do not affect the skeleton muscles and blood irisin levels significantly (42).…”
Section: Table 1 Comparison Of Bfp Fm Lm and Irisin Values After Post...mentioning
confidence: 49%